Audit Sistem Informasi Menggunakan Cobit 4.1 pada PT. Erajaya Swasembada, Tbk. - Wella Wella; Johan Setiawan (Universitas Multimedia Nusantara, 2015)
Main priority aspects of information and communication technologies is given to a control or control mechanisms, both internal and external, to ensure that the report and the decision received and generated by the management decision-making is an honest and have high integrity based on the results of the audit conducted on based systems of information and communication technology. The object of research is the PT Erajaya Swasembada, Tbk. This company was founded in 1990, running a business as a distributor of mobile phones, which have widespread outlets in various cities in Indonesia. Business processes studied include sales, purchasing, finance, and the warehouse. The system used is “Erajaya Live Application Server” version of the July-December 2012 and based ERP (Enterprise Resource Planning). The research was including a General Controls, Boundary Controls, Input Controls, Process Control, Output Controls, Database Control, Application Communication control, and Operating system controls. Data collection methods by performing interviews with the IT managerial departments, distributed questionnaires to the five respondents form of answer was “Yes”, “No” or “Do not Know”, and also observations to the PT Erajaya Swasembada, Tbk. The collected data were analyzed using techniques COBIT 4.1. The results obtained 15 audit findings. The results of maturity model formulation were known domain Plan and Organize at level 4, Acquire and Implement at level 5, Deliver and Support at level 4, Monitor and Evaluate at level 4. Index Terms - Audit, COBIT 4.1, Maturity Model.